(untitled) (Physical Education, Health and Social Sciences, 2025)
Postoperative pain management plays a vital role in patient recovery following orthopedic surgeries. Despite advances in surgical techniques and analgesic therapies, pain management remains a persistent issue. This study aimed to identify the barriers to effective postoperative pain management in orthopedic surgeries across public and private hospitals in Mardan, Pakistan. A descriptive cross-sectional study was conducted over 4–6 months, involving 320 adult patients undergoing orthopedic procedures under general anesthesia. Data were collected through a standardized questionnaire, and pain severity was assessed using the Numerical Rating Scale (NRS). Results indicated that pain assessments were not performed consistently in 52.5% of cases, with significant drug shortages (33.8%) and staffing issues (24.2%) reported in public hospitals. Adverse effects such as drowsiness were observed in 87.5% of patients. Private hospitals showed better organizational support but also revealed underreporting of pain by patients. The findings emphasize the need for improved staff training, standardized pain protocols, and patient education to enhance pain management outcomes.